Functional Categories and Parametric Variation - Ouhalla, Jamal (Theoretical linguistics, 1991)
This book explores the idea that functional categories are the flesh and blood of grammar'. From within the context of the Principles and Parameters framework put forward by Chomsky and others, Jamal Ouhalla develops the argument that much of what we understand by the term grammar and grammatical variation involves functional categories in a crucial way. His main thesis is that most, if not all, of the information which determines the major grammatical processes and relations (movement, agreement, case, etc.) and consequently parametric (or crosslinguistic) variation is associated with functional categories. By identifying parameters with a limited set of lexical properties associated with a well-defined group of functional categories, the book offers a new and highly constrained version of the theory of Lexical Parametrization. Dr Ouhalla begins by identifying a set of lexical properties which distinguish functional categories from substantives, arguing that each of them represents a parameter in its own right. He then goes on to argue on the basis of evidence drawn from a broad range of languages that functional categories, most of which are bound morphemes, behave in important respects like independent syntactic categories, and therefore should be assigned a full categorial status on a par with substantives. The remainder of the book contains detailed discussions of how this conclusion, together with the theory of Lexical Parametrization developed, account naturally for some major typological differences having to do mainly with word order in sentences and noun phrases. Although the various discussions it contains are conducted within the Chomskyan framework, Functional Categories and Parametric Variation is comprehensible to linguists of all theoretical persuasions. It is an original and important contribution to syntactic theory in general.